Perkembangan Pendidikan Islam pada Periode Khulafāur Rāsyidīn dan Implikasinya terhadap Pengembangan Pendidikan Islam di Indonesia - Rony Sandra Yofa Zebua; Miftahul Ihsan; Neneng Nurjanah (Program Pascasarjana Universitas Ibrahimy, 2020)
Religious education for Muslim is Islamic Education originating from Al-Qur’an dan As Sunnah. This study elucidates the dynamic of the change and development of Islamic education in the era after the death of the prophet Muhammad shallallāhu 'alaihi wa sallam, especially in the period of Khulafāur Rāsyidīn. It was revealed how the education system had been implemented in each caliphate and the situation having influenced the educational system. The finding showed that the pattern of the education in the era of caliph Abu Bakar radhīyallāhu ‘anhu was generally still same as the system applied in the era of the prophet of Muhammad shallallāhu 'alaihi wa sallam. The massive development occurred in the period of caliph Umar bin Khatab radhīyallāhu ‘anhu which was continued with the caliph Utsman bin Affan radhīyallāhu ‘anhu. Nevertheless, there were some fundamental changes, especially in the regulation as well as the education method.